Development of Single-Step Affinity Chromatography Protocols for the Purification of Adeno-Associated Viral Vectors. - Carreiras, Rafael Baganha (2020)
Dissertação de Mestrado em Biotecnologia Farmacêutica apresentada à Faculdade de Farmácia